Trans-Frontier Parks: Tourism Development and Poverty Alleviation Vehicles - Lessons from Southern Africa - Zhou, Zibanai (Publishing India Group, 2021)
This study is a surgical examination of the Trans-frontier Conservation Area (TFCA) concept in the frame of Southern Africa using the poverty alleviation construct as the analytical lens. The paper aimed at creating a new narrative, deepening the comprehension of TFCA, and integrating its ecological goals with poverty alleviation. The research touched base with community residents through in-depth interviews to get first-hand experience encounters with reality on the ground. Peace parks have dismally failed to tackle poverty within communities as evidenced by loss of fertile agricultural land, outlawing access to natural resources, destruction of agricultural crops, livestock decimation due to diseases from wild animals, and elusive job prospects. Anecdotal evidence point to local communities` anathema to parks and dismissed the poverty alleviation benefits as an illusion given the huge social capital loss accentuated by involuntary relocation and spike on human-wildlife conflict. Local communities were miffed by prioritisation of ecological needs at the expense of their socio-economic needs; hence logically dismiss peace parks as public relations stunts. Bottom-up approaches are recommended to address poverty issues, coupled with a root and branch shake up of administrative structures in communities and parks hierarchy for fair representation of all the segments of community population.